PENGADUAN PELAYANAN KESEHATAN DI UNIT PELAYANAN INFORMASI DAN KELUHAN (UPIK) - Mahendra, Gerry Katon (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract :Complaint management in the City of Yogyakarta has been integrated through a program called UPIK (Unit Pelayanan Informasi dan Keluhan/Information and Complaint Service), in which all kinds of complaint, health issues included, can be submitted through the government web page. This research aims to describe, analyse, in order to provide recommendations for further improvements of UPIK service management. Using descriptive and qualitative methods, this research analyse complaints submitted to UPIK during 2016. It shows that UPIK significantly helpful in making it easy for government services to manage, categorize, dristributes, as well as monitor the follow up of the submitted complaints.Keywords: public services, health services. Public complaints, upik